Tumor Suppressor miR-184 Enhances Chemosensitivity by Directly Inhibiting SLC7A5 in Retinoblastoma - He, Tian-Geng; Xiao, Zi-Yun; Xing, Yi-Qiao; Yang, Hua-Jing; Qiu, Hong; Chen, Jian-Bin (Frontiers in Oncology, 2019)
The expression patterns and functional roles of miRNAs in Retinoblastoma (RB) is poorly understood, especially these involved in chemoresistance. Here, we validated the expression pattern of 20 potential RB-suppressive miRNAs and confirmed that miR-184 is the most significantly decreased miRNA in human RB tissues, as well as chemoresistant cell line. Bioinformatic and molecular analysis revealed that SLC7A5 has three binding sites of miR-184 and significantly increased in RB tissues. miR-184 negatively correlated with SLC7A5 expression in RB tissues and mainly target position 2494-2513 of the SLC7A5 3’UTR to inhibit its expression. Furthermore, enforced expression of miR-184 reversed the oncogenic roles of SLC7A5 on proliferation, migration and invasion of RB cells. In addition, miR-184 also enhances chemosensitivity of RB cells via inducing apoptosis and G2/M cell cycle arrest. Molecular studies revealed that miR-184 decreased phosphorylation status of known DNA damage repair sensors of the ATR/ATM pathways and induced persistent formation of γH2AX foci depend on targeting SLC7A5, leading to persistent DNA damage. Thus, targeting the miR-184/SLC7A5 pathway will provide new opportunities for drug development to reverse chemotherapeutic resistance in RB.